Investigation on promising progenies of Dragon fruit (Hylocereus spp.) - Karunakaran, G; Sakthivel, T; Lakshmana Reddy, D C; Tripathi, P C; Kalaivanan, D (Journal of Horticultural Sciences, 2024)
Dragon fruit (Hylocereus spp.) is an exotic vine cactus, rich in vitamin C and antioxidants, commonly known as ‘pitaya’ is a weather resilient crop. In order to develop superior varieties, a large number of progenies obtained from open pollinated seedling of cvs. Hiryur red, Vietnam pink and Vietnam red were raised and evaluated. To broaden the genetic base with desired traits, seeds of Hirehalli red and Hirehalli white were irradiated with gamma rays (500, 600 and 700 Gy), EMS (2.25, 2.5 and 2.75%) and sodium azide (0.04, 0.05 and 0.06%) and evaluated for horticultural traits. Three elite progenies such as CHESH-D1, CHESH-D2, and CHESH-D3 were obtained from open pollinated seedlings of cvs. Hiryur red, Vietnam red and Vietnam pink, respectively, and one EMS (2.5%) treated mutant i.e. CHESH-DE were selected based on their morphological and yield traits. The selection CHESH-D1 performed superior with highest fruit weight (507.71 g) and yield (39.50 kg/ pole) compared to CHESH-D2 and CHESH-D3. The biochemical characters namely, TSS (15.35 oB), total sugars (5.95 g), reducing sugars (4.91 g) and betalains (21.2 mg BCE) were recorded highest in CHESH-D2, and one EMS (2.5%) treated mutant from cv. Hirehalli red showed better adaptability and dwarfness. These elite progenies are at final stage of performance assessment to be released as variety in India.
Keywords: Betalains; dwarfness; genetic variability; mutation; reducing sugar